Vulvar Lipoma: A Case Report - Ahmed Reda; Ihab Gomaa (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2018)
Abstract The present study is a case report of vulvar lipoma. The vulva is a rare site for the development of lipomas, and the aim of the study is to determine if the current imaging modalities can diagnose lipomas correctly. A 43-year-old patient presented with a painless, slowly progressive, oval, mobile and non-tender right vulvar mass compressing the vagina and totally covering the introitus. Both the ultrasonography and magnetic resonance imaging (MRI) exams suggested the diagnosis of lipoma. Surgical excision was performed, and the histopathological examination of the mass confirmed a lipoma.